Impact of Helicobacter pylori and metabolic syndrome-related mast cell activation on cardiovascular diseases - Doulberis, Michael; Papaefthymiou, Apostolis; Polyzos, Stergios A.; Boziki, Marina; Kazakos, Evangelos; Tzitiridou-Chatzopoulou, Maria; Vardaka, Elisabeth; Hammrich, Carola; Kulaksiz, Hasan; Riva, Daniele; Kiosses, Christos; Linas, Ioannis; et al. (Frontiers in Gastroenterology, 2024)
Helicobacter pylori, a widely renowned bacterium, has recently gained attention owing to its potential impact on extragastric health. The emergence of research linking H. pylori infection with metabolic syndrome (MetS)-related cardiovascular diseases (CVDs) has raised intriguing questions about the pathogenic linkage and its translational implications for clinicians. MetS encompasses a collection of metabolic abnormalities that considerably elevate the risk of CVDs and cerebrovascular diseases. Emerging evidence supports a potential pathogenetic role of H. pylori for MetS-related disorders through mechanisms implicating chronic smoldering inflammation, insulin resistance (IR), and modulation of immune responses. One intriguing aspect of this possible connection is the role of mast cells (MCs), a subset of immune cells representing innate immune system effector cells. They play a fundamental role in innate immune responses and the modulation of adaptive immunity. Activated MCs are commonly found in patients with MetS-related CVD. Recent studies have also suggested that H. pylori infection may activate MCs, triggering the release of pro-inflammatory mediators that contribute to IR and atherosclerosis. Understanding these intricate interactions at the cellular level provides new insights into the development of therapeutic strategies targeting both H. pylori infection and MetS-related MCs activation. This review investigates the current state of research regarding the potential impact of H. pylori infection and MetS-related MCs activation on the pathophysiology of CVD, thereby opening up new avenues for related research and paving the way for innovative approaches to prevention and treatment in clinical practice